Etiology and management of esophageal impaction in children: A review of 11 years - Baraa Alabd Alrazzak (Thieme Medical and Scientific Publishers Pvt. Ltd., 2013)
Introduction: Esophageal impaction in children is a medical emergency that needs an immediate medical attention. In the last years multiple objects have been detected and were removed endoscopically. In the last decade, Eosinophilic Esophagitis (EoE) has been associated with esophageal stenosis, leading to esophageal impaction with various objects including toys, food, coins and other. Aim: To determine the various objects and symptoms associated with impactions and to develop algorithm that guides Emergency Department Physicians and Primary care Providers when facing such problem in pediatric patient. Material and Methods: A retrospective chart review of all children referred to the pediatric gastroenterology service at Marshall University for FB impaction between 2000 and 2010 was performed. Foreign bodies treated by other specialties were excluded from this review. Clinical and demographic data were retrieved. Results: A total of 291 charts with the diagnosis of foreign body reviewed of which only 126 met the inclusion criteria and considered for final calculation. Male/Female ratio and mean age were 1.17:1.0, and 3.65 ± 0.75 years, respectively. Time of impaction before ER evaluation was: < 24hrs in 75 patients, >24hrs in 17 and in 34 the time of ingestion was not known. Radiology was performed in 118 patients, of whom 1 had pneumo-mediastinum and 1 had pneumothorax. Endoscopic localization of the objects showed: 81- proximal, 23- middle esophagus, and 22- in the distal esophagus. The esophageal mucosa showed non-specific changes in 37 patients, 5 with EoE features, 1 patient with hiatal hernia, 1 patient with candidiasis, and in 5 pts had no mucosal description. Conclusion: Children with foreign body in the esophagus are commonly seen in our Hospital ER. Those children may harbor undiagnosed medical conditions that will need future therapy. Careful endoscopic assessment with mucosal biopsies is needed to diagnose those conditions earlier. Referral to a GI specialist may be warranted.